Uncoupled Two Agents Modeling Via Bilinear Optimal Control - R. Heru Tjahjana (Department of Mathematics, Faculty of Sciences and Technology, UIN Syarif Hidayatullah, 2022)
In this paper, uncoupled two agents modeling is proposed using an optimal bilinear control approach. The model is proposed using assumptions: an absence of the multi agent leader, each agent cannot control the others, each agent never collides with the others, and each agent has the same properties. The special functional cost consisting of a repellent cost is considered. The Pontryagin Maximum Principle is used to determine the optimal path for each agent. After control and optimal path for each agent are obtained some of the simulation results are exposed in this paper.Keywords: uncoupled agent; modeling; bilinear system. AbstrakDalam penelitian ini, pemodelan dua agen yang tidak berpasangan disajikan dengan pendekatan kontrol optimal bilinear. Model yang diusulkan dalam paper ini ditulis dengan asumsi: tidak adanya pemimpin dalam sistem multi agen, setiap agen tidak dapat mengendalikan atau mempengaruhi agen yang lain, setiap agen tiak boleh bertabrakan satu sama lain, dan para agen mempunyai sifat-sifat yang identik. Fungsional biaya khusus yang membuat para agen tidak bertabrakan dipertimbangkan dalam penulisan paper ini. Prinsip maksimum Pontryagin digunakan dalam penentuan lintasan optimal dari para agen. Beberapa hasil simulasi disajikan dalam paper ini.Kata Kunci: agen tak berpasangan; pemodelan; sistem bilinear.